High‐Efficiency Photovoltaic Devices using Trap‐Controlled Quantum‐Dot Ink prepared via Phase‐Transfer Exchange. Issue 19 (7th March 2017) - Aqoma, Havid; Al Mubarok, Muhibullah; Hadmojo, Wisnu Tantyo; Lee, Eun‐Hye; Kim, Tae‐Wook; Ahn, Tae Kyu; Oh, Seung‐Hwan; Jang, Sung‐Yeon
Abstract : Colloidal‐quantum‐dot (CQD) photovoltaic devices are promising candidates for low‐cost power sources owing to their low‐temperature solution processability and bandgap tunability. A power conversion efficiency (PCE) of >10% is achieved for these devices; however, there are several remaining obstacles to their commercialization, including their high energy loss due to surface trap states and the complexity of the multiple‐step CQD‐layer‐deposition process. Herein, high‐efficiency photovoltaic devices prepared with CQD‐ink using a phase‐transfer‐exchange (PTE) method are reported. Using CQD‐ink, the fabrication of active layers by single‐step coating and the suppression of surface trap states are achieved simultaneously. The CQD‐ink photovoltaic devices achieve much higher PCEs (10.15% with a certified PCE of 9.61%) than the control devices (7.85%) owing to improved charge drift and diffusion. Notably, the CQD‐ink devices show much lower energy loss than other reported high‐efficiency CQD devices. This result reveals that the PTE method is an effective strategy for controlling trap states in CQDs. Abstract : A colloidal quantum dot (CQD)‐ink is developed by phase‐transfer exchange, enabling the fabrication of active layers by single‐step coating to achieve a thick film. The CQD‐ink exhibits low surface traps due to improvement of surface passivation. Thus, incorporating the CQD‐ink into devices shows high efficiency and low voltage loss.